2013
DOI: 10.1007/s00217-013-2097-4
|View full text |Cite
|
Sign up to set email alerts
|

Structuring and texturing gluten-free pasta: egg albumen or whey proteins?

Abstract: The effects of adding egg albumen or whey proteins to pasta made from parboiled rice flour were 17 investigated. Pasta quality was evaluated in terms of color, of furosine content, and of cooking properties (water absorption, cooking loss, and consistency at the optimal cooking time). The 19 surface heterogeneity of the cooked and uncooked materials was studied, and some starch properties 20 (pasting properties, starch susceptibility to alpha-amylase hydrolysis) were assessed, along with the 21 features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 22 publications
7
56
0
1
Order By: Relevance
“…Addition of urea to the buffer/saline extraction buffer resulted in a significant increase in solubilized protein in all samples suggesting that hydrophobic interactions among proteins were very relevant to the structure of the protein network in pasta samples (Figure ). A similar picture was observed in previous investigations on GF pasta (Mariotti and others ; Cabrera‐Chavez and others ; Marti and others ). When both urea and DTT were present in the extraction medium, the amount of soluble proteins further increased in a very marked way in all samples (Figure ), suggesting that interprotein disulfides play a fundamental role in stabilizing the structure of protein network.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Addition of urea to the buffer/saline extraction buffer resulted in a significant increase in solubilized protein in all samples suggesting that hydrophobic interactions among proteins were very relevant to the structure of the protein network in pasta samples (Figure ). A similar picture was observed in previous investigations on GF pasta (Mariotti and others ; Cabrera‐Chavez and others ; Marti and others ). When both urea and DTT were present in the extraction medium, the amount of soluble proteins further increased in a very marked way in all samples (Figure ), suggesting that interprotein disulfides play a fundamental role in stabilizing the structure of protein network.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, most of the commonly used refined GF flours have naturally lower protein contents than wheat‐based products (Hager and others ). Therefore, the use of whole grain (see I2), pseudocereals (see I4) (Alvarez‐Jubete and others ), pulses, or milk/egg proteins (Marti and others ) is recommended to improve the technological performance and the nutritional profile of GF pasta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, a total of five detecting sensors and two reference electrodes were used, separated into two arrays according to membrane charge: hybrid (CT0, CA0, and AAE) and positive (C00 and AE1). Studies on protein aggregation events in the extruded products were carried out by measuring soluble proteins from extruded products in various buffers as described by Marti et al (2014). Extruded products were milled into fine flour, of which 5 g was suspended in 50 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…In wheat pasta the cooking loss is typically lower than 8%, but the lack of gluten in gluten-free pasta can cause an increase in CL and a decrease in firmness because the starch polymers are less linked to the matrix (Marti et al, 2014). Also, Tudorica et al (2002) showed that increasing of cooking loss could be caused by fibers which use a higher water quantity.…”
Section: Cooking Lossmentioning
confidence: 99%